IDENTIFIKASI ALAT BANTU PENANGKAPAN IKAN PADA BAGAN APUNG DI PERAIRAN KRUENG RAYA - Junaidi M. Affan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
Lift-nets is one of the important fisheries sectors that become the source of coastal comunity livelihood in Krueng Raya, Aceh Besar. The operation of the fishing gear is always supported by the fishing tools that can assist the operation process, as well as the lift-nets that exist in the Krueng Raya area. The main fishing tools on the lift-nets in Krueng Raya are lights, generator and roller. The lack of data and information on the characteristics of fishing equipment becomes an obstacle to improve the development of lift-nets. This study aims to identify fishing equipment used in lift-nets at Krueng Raya. The data were collected by interviewed and directed field observation. Descriptive analysis showed the fishing equipment used in lift-nets in Krueng Raya used neon and mercury lamps, the generator capacity is 15000 watts and roller made of bayur wood (Pterospermum javanicum). The updates of the fishing equipment used in lift-nets at Krueng Rayacan still be made. Kata kunci: Krueng Raya, Lift Net